2021
DOI: 10.1186/s40364-021-00275-y
|View full text |Cite
|
Sign up to set email alerts
|

TOX as a potential target for immunotherapy in lymphocytic malignancies

Abstract: TOX (thymocyte selection-associated HMG BOX) is a member of a family of transcriptional factors that contain the highly conserved high mobility group box (HMG-box) region. Increasing studies have shown that TOX is involved in maintaining tumors and promoting T cell exhaustion. In this review, we summarized the biological functions of TOX and its contribution as related to lymphocytic malignancies. We also discussed the potential role of TOX as an immune biomarker and target in immunotherapy for hematological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 53 publications
(51 reference statements)
0
36
0
Order By: Relevance
“…It is important for the differentiation of subsets of T-cells and natural killer cells. It is also implicated in tumor development as it induces CD8+ T-cell exhaustion by weakening their effector functions [ 18 ]. T-cell exhaustion occurs when cytotoxic T-cells are constantly activated, such as in cancer and chronic viral infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important for the differentiation of subsets of T-cells and natural killer cells. It is also implicated in tumor development as it induces CD8+ T-cell exhaustion by weakening their effector functions [ 18 ]. T-cell exhaustion occurs when cytotoxic T-cells are constantly activated, such as in cancer and chronic viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…TOX is overexpressed in tumor infiltrating cells and is associated with an increased expression of the inhibitory programmed-death protein. In malignant T-cell lymphomas, TOX is highly expressed in MF, T-lymphoblastic lymphoma, angioimmunoblastic T-cell lymphoma, and in a lower level in peripheral T-cell lymphoma and other lymphomas [ 18 , 19 , 20 ]. What drives TOX expression and its role in MF is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers for AML outcome, particularly those related to immune suppression, which often occurs in cancer immune escape, are far from clear. Recent studies have shown that TOX is a crucial transcription factor that contributes to T cell exhaustion and is involved in tumor development (16,23). However, how TOX is altered in AML remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TOX includes four subfamily members (TOX1-4, TOX1 is also known as TOX) (15). TOX is a crucial transcription factor related to the development of malignancies and contributing to CD8+ T cell exhaustion in patients with solid tumors (16)(17)(18). For example, TOX is positively correlated with larger tumor size, lower differentiation, later tumor node metastasis (TNM) stage, and facilitating endocytic recycling of PD-1 (17).…”
Section: Introductionmentioning
confidence: 99%
“…The TOX protein family consists of four members that all function as transcription factors: TOX (also known as TOX1), TOX2, TOX3 and TOX4. 32 TOX and/or TOX2 are involved in many early lymphoid developmental processes, including positive selection in thymocytes, early development of CD4+ T and NK cells, development of innate lymphoid cells and lymph node organogenesis. 33–35 More important in the setting of our study, they are essential for the development of Tfh cells and the induction of exhaustion in both CD4+ and CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%